Police recruits, moral judgements and an empathetic policing - Millie, Andrew (Criminology & criminal justice, 2024)
In this article, we consider the moral judgements of new recruits to the police by drawing on two stages of semi-structured interviews with recruits over their first 6 months working for Lancashire Constabulary in England. The article contributes to the literature by providing insights into the moral thinking of police officers at the very early stages of their career. The discussion is supported by relevant criminological and philosophical literature as appropriate. Evidence is presented that there is more to the recruits’ moral judgements than a simple reflection of codified standards of behaviour as taught in police training. Their experiences reflect greater complexity than straightforward socialisation into existing cultures. The recruits emphasise an inclusive empathy and greater compassion for others – often irrespective of what those others have done. An empathetic policing is suggested that could challenge assumed dominant cultures and may be a way to encourage greater engagement with the moral value of police action and inaction.